A comparative study on the ballistic performance of aramid and aluminum honeycomb sandwich structures. (1st November 2022) - Rathod, Saurabh; Khaire, Nikhil; Tiwari, Gaurav
Highlights: Impact response of AHS and AlHS sandwich structure was compared. Ballistic limits and EA was obtained against conical and hemispherical projectile. EA was enhanced by increasing cell and facesheet thickness, reverse for cell size. A higher specific energy absorption was obtained in AHS as compared to AlHS. Abstract: This study investigated the perforation phenomenon of aramid and aluminium honeycomb sandwich structures under high-velocity impacts and compared the impact responses experimentally and numerically. The dimension of the face sheets used was 1 mm in thickness and 220 mm in diameter, and for both the honeycomb cores, the cell thickness of 0.05 mm and the cell size of 3.2 mm was used. Ballistic impact tests were conducted by employing a pneumatic air gun to study damage behavior and failure modes under different impact velocities between 35 m/s and 150 m/s using conical shaped and hemispherical shaped projectiles. Three-dimensional finite element models were implemented in ABAQUS/Explicit to model sandwich panels. The numerical model was validated with experimental data and, subsequently, the numerical study was further extended to study the effects of different geometrical parameters affecting the impact response of sandwich structures. The results showed that for the ballistic limit, sandwich structure having an aluminium honeycomb core performed better than the aramid honeycomb core by 3.09% and 2.5% against conical and hemispherical projectiles, respectively. However, the aramid honeycomb structure was proven to be more efficient than the aluminum honeycomb structure in terms of energy absorption and specific energy absorption.